Predicting current and future potential distribution of Cynaeus angustus (Coleoptera: Tenebrionidae) in global scale using the MaxEnt model. (March 2023) - Zhao, Chao; Bai, Chunqi; Wang, Dianxuan
Abstract: The larger black flour beetle, Cynaeus angustus (LeConte), as a fauna extending storage insect has rapidly spread globally from its native North America to other continents and countries in the last three decades. Based on the occurrence records and environmental variables, the current and future potential distribution on a global scale are predicted using MaxEnt model. The results showed that the current suitable area involved in China, South Korea, North Korea, Japan, Kazakhstan, Afghanistan, Australia, Argentina, the Republic of South Africa, North America, and most of European countries. Under future climate change scenarios, this insect is predicted to remarkably expand its fauna range to the north and Representative Concentration Pathways 8.5 (RCP8.5) provides the largest expansion, and the suitable area expands in the northern hemisphere whereas contraction in the southern hemisphere. The annual mean temperature, temperature annual range were the key factors influencing the potential distribution of C. angustus . The results of this study provide basic data for pest monitoring, early warning measures, and quarantine strategies in high-risk countries. Highlights: The current and future potential distribution of Cynaeus angustus on a global scale are predicted using MaxEnt model. Under current climate, suitable area for  C. angustus  involved in all the continents except Antarctica. Under future climate, this pest is predicted to remarkably expand its fauna range to the north. This study is meaningful for pest monitoring, early warning measures, and quarantine strategies in high-risk countries.